2001
DOI: 10.1054/bjoc.2001.2017
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of wild-type p53 by a dominant negative mutant renders MCF-7 cells resistant to tubulin-binding agent cytotoxicity

Abstract: SummaryThe present study was performed to gain insight into the role of p53 on the cytotoxicity of tubulin-binding agents (TBA) on cancer cells. Drug sensitivity, cell cycle distribution and drug-induced apoptosis were compared in 2 lines derived from the mammary adenocarcinoma MCF-7: the MN-1 cell line containing wild-type p53 (wt-p53) and the MDD2 line, containing a dominant negative variant of the p53 protein (mut-p53). The MDD2 cell line was significantly more resistant to the cytotoxic effects of vinblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
29
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 26 publications
3
29
0
1
Order By: Relevance
“…We have previously shown that MDD2 cells displayed 31.5-fold resistance to paclitaxel (MN-1 IC 50 : 7.6 nM; MDD2 IC 50 : 240 nM) and 50-fold resistance to vinblastine (MN-1 IC 50 : 6.8 nM; MDD2 IC 50 : 340 nM) in comparison with MN-1 cells (Galmarini et al, 2001). …”
Section: Cell Linesmentioning
confidence: 97%
See 4 more Smart Citations
“…We have previously shown that MDD2 cells displayed 31.5-fold resistance to paclitaxel (MN-1 IC 50 : 7.6 nM; MDD2 IC 50 : 240 nM) and 50-fold resistance to vinblastine (MN-1 IC 50 : 6.8 nM; MDD2 IC 50 : 340 nM) in comparison with MN-1 cells (Galmarini et al, 2001). …”
Section: Cell Linesmentioning
confidence: 97%
“…HCT116 p53À/À is a cell line derived from colorectal carcinoma in which two promoterless targeting vectors were used to disrupt sequentially the two p53 alleles (Bunz et al, 1998). All cell lines were cultured as previously described (Galmarini et al, 2001).…”
Section: Cell Linesmentioning
confidence: 99%
See 3 more Smart Citations